Subjective well-being in directives of the Oriente´s Transport Company (Encuentros, 2016)
This scientific research has the objective of identifying the indicators for Subjective Well-being (SWB) in managers. Multiple cases qualitative study with managers of Company the Oriente´s Transport using the techniques: interviews in depth, participant observation, Psychological Well-being Scale and content analysis. The results allowed defining as indicators: the performance effective in manager´s role in the organization; the effect of the managing activity in others life domain; the harmonic integration of the values; the subjective configuration of the managing activity and the psychological well-being. That allowed proposing a strategy of psychological intervention, based on the Appreciative Inquiry for improve SWB in managers of this company that at the present moment is in application process. Keywords: Subjective Well-being, Managers, Appreciative Inquiry, Psychological Intervention, Organizational Psychology